Towards global missional leadership : a journey through leadership paradigm shift in the mission of God - Franklin, Kirk (Regnum practitioner series., 2017)
The depth and complexity of interconnected global issues facing church and mission leadership today cannot be ignored. Leaders within global church and mission movements are challenged to respond to effects of globalization and other factors upon the mission of God. Rather than modifying existing models of leadership, there is critical need to understand an emerging global missional leadership paradigm against the backdrop of a world full of discontinuous change. The purpose of this book is to shine light on key elements contributing to the development of a global missional mindset among leadership in church and mission movements within the context of the missio Dei.